Handbook of statistical data editing and imputation - Waal, Ton de; Pannekoek, Jeroen 1951-; Scholtus, Sander 1983- (Hoboken, New Jersey Wiley, 2011)
Handbook of Statistical Data Editing and Imputation is an essential reference for survey researchers working in the fields of business, economics, government, and the social sciences who gather, analyze, and draw results from data. It is also a suitable supplement for courses on survey methods at the upper-undergraduate and graduate levels.
Includes bibliographical references and index.
Keywords: Statistics -- Standards; Data editing; Data integrity; Quality control; Statistical services -- Evaluation